Pengelolaan Program Ekstrakurikuler di Sekolah Negeri dan Swasta Sebagai Upaya Pengembangan Karakter Siswa - Gina Amalia; Nabilla Nur Fauziah; Nurlaila Ramadhani; Agus Mulyana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to determine the management of extracurriculars in public and private elementary schools, as well as the role of extracurriculars in developing the character of elementary school students. This research uses a type of qualitative research through exposure that describes a phenomenon that occurs. This research was carried out using a descriptive method by explaining in detail about a phenomenon. The research techniques used are observation, interviews and literature study. Observations and interviews were carried out by visiting public and private elementary schools directly by observing the extracurricular activities carried out and conducting an interview process with the extracurricular supervisors and school principals.